2011
DOI: 10.1111/j.1365-2710.2011.01291.x
|View full text |Cite
|
Sign up to set email alerts
|

High risk of cross-reactivity between vancomycin and sequential teicoplanin therapy

Abstract: Teicoplanin, used as an alternative in cases of vancomycin intolerance, was associated with a high incidence of ADRs and haematological reactions, most notably neutropenia. This high rate of ADRs suggests cross-reactivity between the two glycopeptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…A cross allergic reaction between vancomycin and other glycopeptides has been described for teicoplanin but not for other glycopeptides (59). …”
mentioning
confidence: 99%
“…A cross allergic reaction between vancomycin and other glycopeptides has been described for teicoplanin but not for other glycopeptides (59). …”
mentioning
confidence: 99%
“…After coronary artery bypass graft surgery he developed sternal dehiscence and high-grade fever; his white blood cell count was 10,100/mL and Creactive protein was 8.8 mg/dL. While the sequential administration of teicoplanin after vancomycin-induced adverse drug reactions may increase the incidence of drug reactions elicited by teicoplanin due to the cross-reactivity of these drugs [2,6], our patient had not undergone prior treatment with vancomycin. His teicoplanin trough levels were monitored to stay within the therapeutic range (10-20 mg/mL).…”
Section: Teicoplanin-induced Purpuric Eruption With Leukocytoclastic mentioning
confidence: 87%
“…In 1992, Ruiz-Maldonado et al proposed diagnostic criteria for HI [2]. nervous and/or musculoskeletal abnormalities [2]. nervous and/or musculoskeletal abnormalities [2].…”
Section: Pigmentary Mosaicism Of the Hypopigmented Type (Hypomelanosimentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that the alternate use of TEC in cases of VAN intolerance was associated with a high incidence of drug-related adverse events, most notably neutropenia (36,37). Therefore, the potential cross-reactivity between these 2 glycopeptides remains to be clarified in future studies.…”
Section: Discussionmentioning
confidence: 99%